2018
DOI: 10.1155/2018/4595982
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Thermal Skin Aging Activity of Aqueous Extracts Derived from Apple Mint (Mentha suaveolens Ehrh.) in Human Dermal Fibroblasts

Abstract: Thermal skin aging refers to skin aging induced by heat shock treatment. Apple mint (Mentha suaveolens Ehrh.) has been used as a folk medicine to treat various diseases. However, the activity of apple mint in thermal skin aging has yet to be investigated. In this study, we conducted various biological assays to demonstrate the anti-thermal skin aging activity of extracts of apple mint leaves (ALE). As a result, ALE showed significant antioxidant activities and inhibited the production of reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been reported that it possesses various biological properties such as antioxidant, antimicrobial, antifungal, anti-inflammatory, and anticancer [1113]. In a previous study, we have observed that M. suaveolens extract exerted the antithermal skin-aging effect in human dermal fibroblasts [14]. However, the cytoprotective activity of M. suaveolens against oxidative stress-induced cell damage in keratinocytes has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that it possesses various biological properties such as antioxidant, antimicrobial, antifungal, anti-inflammatory, and anticancer [1113]. In a previous study, we have observed that M. suaveolens extract exerted the antithermal skin-aging effect in human dermal fibroblasts [14]. However, the cytoprotective activity of M. suaveolens against oxidative stress-induced cell damage in keratinocytes has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Apple mint (Mentha suaveolens) essential oil possesses cell regenerative, antioxidant, antiseptic, and insecticidal properties. The oil's anti-aging activity has been demonstrated [35] - [36]. Therefore, this oil and clay mixture could also be an effective aid in acne treatment.…”
Section: Environment Technology Resources Rezekne Latvia Proceedings ...mentioning
confidence: 99%
“…Heat-induced expression of MMP-1, MMP-3, MMP-10, MMP-12, and MMP-13 in human dermal fibroblast was significantly inhibited by 100 μg/mL of apple mint leaves extract (ALE). Also, the activity of p-ERK, p-JNK, p-p38, and the expression of IL-8 were inhibited in a dose-dependent manner in HDF cells treated with ALE [ 183 ].…”
Section: Properties Of the Mentha Genusmentioning
confidence: 99%